The Influence of Project-Based Learning on Students’ Creative Thinking in Poetry Writing - Gita Fitria; Asri Yulianda; Yuannisah Aini Nasution (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study analyzes the impact of the Project-Based Learning (PjBL) model on students’ creative thinking skills in poetry writing among seventh-grade students at MTs Negeri 2 Hadundung Village. A quasi-experimental design with a pretest-posttest control group was used, involving two classes: an experimental class implementing PjBL and a control class using conventional methods. Data were collected through creative thinking ability tests, observations, and documentation, with creativity measured based on originality, fluency, and elaboration in poetry writing. The results show a significant improvement in students’ creative thinking skills after implementing PjBL. The experimental class demonstrated higher posttest scores than the control class, indicating that PjBL effectively enhances students’ ability to generate unique and expressive poetry. Furthermore, students in the experimental class exhibited greater motivation and active participation during learning, which contributed to more varied and sophisticated poetic expressions. The analysis using a t-test showed a significance value of p = 0.002 (p < 0.05), confirming that PjBL had a statistically significant effect on students’ creativity. Beyond academic improvement, PjBL encouraged collaborative learning and real-world problem-solving, allowing students to explore ideas more freely. This method promoted student-centered learning, where learners engaged in hands-on experiences, deepening their understanding of poetry composition. The findings suggest that PjBL is a highly effective approach to fostering creative thinking and enhancing literary skills in students.